2006
DOI: 10.1147/sj.452.0361
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionary impact of XML on biomedical information interoperability

Abstract: The use of Extensible Markup Language (XML) to implement data sharing and semantic interoperability in healthcare and life sciences has become ubiquitous in recent years. Because in many areas there was no preexisting data format, XML has been readily embraced and is having a great impact. Biomedical data is very heterogeneous, varying from administrative information to clinical data, and recently to genomic data, making information exchange a great challenge. In particular, it is hard to achieve semantic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…ODM does not specify the use of specific clinical items such as CDASH, nor does it provide a specific mechanism for pointing to the source of a particular CDE. Instead, ODM provides a hierarchical container for defining clinical data items according to the needs of a given study [65], as shown in Figure 3. The lack of a source definition for a clinical data item was highlighted when the ISO 11179 DECs were found missing from the ODM model [13].…”
Section: 0 Resultsmentioning
confidence: 99%
“…ODM does not specify the use of specific clinical items such as CDASH, nor does it provide a specific mechanism for pointing to the source of a particular CDE. Instead, ODM provides a hierarchical container for defining clinical data items according to the needs of a given study [65], as shown in Figure 3. The lack of a source definition for a clinical data item was highlighted when the ISO 11179 DECs were found missing from the ODM model [13].…”
Section: 0 Resultsmentioning
confidence: 99%
“…For example, a query containing a join operation between two classes of objects is possible only if the classes are associated in the model. Model creators annotate their object-oriented models and the model’s classes and attributes with concepts from the EVS service using a tool called SIW [37], thus creating common data elements. A common data element is also associated with a value domain, which specifies a representation of said data element using concrete data types (e.g., float, integer) and permissible values (e.g., a data element can take values between −1 and +5, or can take a value from a set of discrete values).…”
Section: Cabig Interoperability Infrastructurementioning
confidence: 99%
“…There are many reasons for this -lack of time, resources, interest, and incentives for data sharing are all cited as barriers to true information exchange [35,36]. This varies from scientific community to community, though there have been extensive calls for data sharing in the broader scientific literature [37,38]. It is often argued by scientists themselves that most information sharing is done in the form of peer-reviewed workshop papers, conference presentations, journal articles, and informal networks; therefore, sharing "raw data" is not feasible, since it would require setting up a dedicatee archive, responding to many individual requests, and other mechanisms that may be time-consuming.…”
Section: Challenges and Concernsmentioning
confidence: 99%